The power and the promise of epigenetic drugs in oncology - Scandolara, Thalita Basso; Siqueira, Isabelle Vasconcelos Menegoy; Ribeiro Pinto, Luis Felipe; Soares-Lima, Sheila Coelho (Frontiers in Genetics, 2026)
Epigenetic dysregulation is commonly observed in cancer and has been shown to contribute to different steps of carcinogenesis, from initiation, making cells more prone to transformation, to progression and treatment resistance. Therefore, based on their frequency, relevance and reversibility, epigenetic alterations are promising therapeutic targets in oncology. Although the concept of targeting epigenetic mechanisms is not new, recent advances have been made in reducing toxicity, augmenting specificity, diversifying the targets and combining therapies. In this scoping review, we introduce the main epigenetic mechanisms of gene expression regulation and bring the current knowledge on available epidrugs, focusing on their mechanisms of action and ongoing clinical trials.